Sport psychiatry and psychotherapeutic intervention, circa 2016. (1st November 2016) - Stillman, Mark A.; Brown, Tyler; Ritvo, Eva C.; Glick, Ira D.
Abstract: The focus of this paper is to provide an update on the use of psychotherapy as a treatment in sport psychiatry, and the use of this approach to address common psychiatric issues encountered with this population. Specifically, family therapy, individual therapy, and group psychotherapy prescribed alone, or in combination with medication, will be examined as methods to manage issues/disorders often associated with athletes. These include obsessive-compulsive rituals and perfectionism, and aggressive and risky behaviours, such as gambling, infidelity, substance use, and suicidal ideation, narcissism, and aggression in the context of individual and team competitive sports.